New usability guidelines with implementation ways of mobile learning application based on mobile learning usability attributes - Hujainah, Fadhl; Halina, Dahlan; Al-haimi, Basheer; Hujainah, Ammar; Al-Bashiri, Hael; Abdulgabber, Mansoor Abdullateef (Informatics Publishing Limited, 2016)
Objectives: This work aims to propose new improvements to mobile learning application. These improvements are presented by proposing new guidelines of mobile learning application along with their implementation ways and propose mapping each proposed guideline with mobile learning usability attributes. Methods/Statistical Analysis: The researchers review the existing usability guidelines for mobile learning application in related work in order to identify the current challenges. Proposed solutions are presented to solve the identified challenges by producing new guidelines along with their implementation ways. Also, the researcher proposed mapping these guidelines with mobile usability learning attributes to ensure that proposed guidelines covers the usability issues of mobile learning. Moreover, the proposed improvements are evaluated using expert usability review method to measure its acceptance. Findings: Expert usability review method is used to evaluate the proposed guidelines, proposed implementation way of guidelines, and proposed mapping guidelines with usability mobile for mobile learning application. The researchers used quantitative approach for the data collection purpose. Evaluation result shows that 81% of the participated experts’ opinions are agreed with the proposed improvements of the usability guidelines based on produced guidelines, proposed ways to implement each guideline, and proposed mapping the guidelines with mobile learning usability attributes. Followed by 11% of the experts’ opinion are undecided and only 7% of the experts’ opinion are disagree the proposed improvement of the usability. Application/Improvements: From findings, it is obvious that the proposed improvements can be used for developing mobile learning application with meeting usability standards efficiently. New guideline can be added in order to handle new issues that might be appeared in the future.